2014
DOI: 10.1097/aog.0000000000000465
|View full text |Cite
|
Sign up to set email alerts
|

Cost Savings of Red Cell Salvage During Cesarean Delivery

Abstract: Setup of intraoperative cell salvage during cesarean delivery is cost-saving and should be considered only when there is a predictably high probability of transfusion or when a massive transfusion is reasonably likely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…Although beyond the scope of this article, a detailed cost analysis should be performed to elucidate the point at which intraoperative blood salvage becomes costeffective in postpartum hemorrhage. Albright and colleagues 15 have demonstrated that intraoperative blood salvage is only cost-saving in cesarean delivery when there is a high probability of blood loss, such as when two to three intraoperative blood salvage units are reinfused. There are the costs of the disposables and the technologists' time that are associated with a standby intraoperative blood salvage case, and even more disposables are required should a reinfusion of intraoperative blood salvage occur; these costs need to be balanced against that of allogeneic RBC units and their potential for adverse events.…”
Section: Commentsmentioning
confidence: 98%
“…Although beyond the scope of this article, a detailed cost analysis should be performed to elucidate the point at which intraoperative blood salvage becomes costeffective in postpartum hemorrhage. Albright and colleagues 15 have demonstrated that intraoperative blood salvage is only cost-saving in cesarean delivery when there is a high probability of blood loss, such as when two to three intraoperative blood salvage units are reinfused. There are the costs of the disposables and the technologists' time that are associated with a standby intraoperative blood salvage case, and even more disposables are required should a reinfusion of intraoperative blood salvage occur; these costs need to be balanced against that of allogeneic RBC units and their potential for adverse events.…”
Section: Commentsmentioning
confidence: 98%
“…Whilst cell salvage and retransfusion are viewed as relatively expensive and labor intensive, autologous cell salvage is now being adopted in many obstetric centers managing PAS disorders, with observational studies showing improved outcomes and reduced need for allogenic blood transfusion, without an increase in adverse outcomes . Regarding cost analysis, a recent study demonstrated that intraoperative cell salvage during cesarean delivery for invasive placentation justified its use where the probability of requiring packed red cell transfusion of two units was 75% …”
Section: Intraoperative Considerationsmentioning
confidence: 99%
“…[84][85][86] Regarding cost analysis, a recent study demonstrated that intraoperative cell salvage during cesarean delivery for invasive placentation justified its use where the probability of requiring packed red cell transfusion of two units was 75%. 87 It is important that suctioned contaminants are kept to an absolute minimum, including amniotic fluid, vernix, microorganisms, fetal blood, and exogenous surgical solutions such as contemporary hemostatics. 88 These may not be filtered adequately by cell salvage equipment and may be reinfused directly into the maternal circulation with theoretical complications including embolism, isoimmunization and thrombosis.…”
Section: Cell Salvagementioning
confidence: 99%
“…Also, use of PACS, particularly along with allogeneic blood transfusion, appears cost saving and cost effective in various settings, including obstetric, general surgical, and some pediatric surgical indications. [43][44][45] The use of PACS for cases at high risk for obstetric hemorrhage was found to be economically reasonable, while routine PACS use for all cesarean deliveries was not ascertained as cost effective. 46 Despite the recommendations from perioperative transfusion guidelines supporting PACS, the recent decline in PACS observed in the past decade probably reflects overall optimization of transfusion practice.…”
Section: Discussionmentioning
confidence: 98%